ANÁLISE DA EXPRESSÃO DOS RECEPTORES DA SOMATOSTATINA (SST1-5) E DA DOPAMINA (DR2) EM ADENOMAS HIPOFISÁRIOS - Nunes, Bruno de Almeida (2012)
Pituitary tumors represent 15% of intracranial neoplasms and are usually benign. The treatment primary is surgical resection with exception for prolactinomas because dopamine agonists are very effective in the treatment these tumors. If surgery does not lead to healing, it is necessary other therapeutic strategy in a attempt to control hormone levels and tumor size reduction. The radiotherapy and medical treatment with somatostatin analogs and agonist dopamine are often used. The study aimed to analyze the presence, distribution and frequency of somatostatin receptor and dopamine receptor (DR2) in pituitary adenomas, and compared their mRNA expression and protein expression. We studied 38 patients with pituitary adenomas. The GH-secreting adenomas showed immunoreactivity more frequent SST2 and SST3 present in 100% of the tumors followed SST5, SST4 and SST1 respectively. Clinically nonfunctioning adenomas SST3 receptor was most widely distributed, present in 13 of 14 tumors followed SST2, SST4, SST1 and SST5 respectively. The mRNA expression of SST2 and SST5 receptor was present in all pituitary adenomas with higher expression of SST2. The DR2 receptor was present and 85% of samples analyzed. In conclusion, the high expression of SST2 in somatotropinomas support the possibility of the use of octreotide as an adjunct therapy in the treatment of acromegalic patients. Patients with clinically nonfunctioning adenomas showed expression of somatostatin receptor and dopamine which indicates the possibility of treating these patients with the somatostatin analogues and / or dopamine agonists.